OPTIMIZING THE APPLICATION OF STUDENT CHARACTERS IN LEARNING SOCIAL SCIENCES - Dewi Sri Wahyuni; Indah Suciati; Nasim Taha (Indonesian Journal of Education (INJOE), 2023)
This literature review aims to look at optimizing the application of student character in social studies learning. Social studies learning has an important role in forming student character. Students who have mental strength and good morals will certainly be able to have a personality with character. This can differentiate him from other students. Social studies learning in forming students' character is certainly not an easy thing, it requires continuous struggle to produce results that are in line with national education goals. One of the main objectives of social studies learning in schools is to be responsible for building students' character to become good and useful citizens. Social studies education is actually very closely related to character education. This can be seen from the formulation and objectives, that character education or values education also aims to make students become good citizens. Social studies learning has similarities with character education in that both have the aim of making students good citizens, concerned about existing social and environmental problems, and also both have a high sense of nationality.